2009
DOI: 10.1002/mnfr.200900008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heat treatment of dairy products by MALDI‐TOF‐MS

Abstract: The formation of the Amadori product from lactose (protein lactosylation) is a major parameter to evaluate the quality of processed milk. Here, MALDI-TOF-MS was used for the relative quantification of lactose-adducts in heated milk. Milk was heated at a temperature of 70, 80, and 100 degrees C between 0 and 300 min, diluted, and subjected directly to MALDI-TOF-MS. The lactosylation rate of alpha-lactalbumin increased with increasing reaction temperature and time. The results correlated well with established ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…By using a proteomic approach, we recently demonstrated that these and other water-soluble milk proteins (33 in total number) essential for nutrient delivery, defense against pathogens and cellular proliferation become lactosylated during milk processing [37]. Their nature and modification extent have been associated with the harshness of product manufacturing [22][23][24][25][26][27][28][29][30][31][32]37], putatively having possible consequences on protein functional activity, digestibility, allergenic potential and essential amino acid bioavailability. In fact, the Maillard reaction may modify protein residues involved in biocatalysis or affecting polypeptide three-dimensional structure [12,38,39], thus ultimately influencing aliment functional properties.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…By using a proteomic approach, we recently demonstrated that these and other water-soluble milk proteins (33 in total number) essential for nutrient delivery, defense against pathogens and cellular proliferation become lactosylated during milk processing [37]. Their nature and modification extent have been associated with the harshness of product manufacturing [22][23][24][25][26][27][28][29][30][31][32]37], putatively having possible consequences on protein functional activity, digestibility, allergenic potential and essential amino acid bioavailability. In fact, the Maillard reaction may modify protein residues involved in biocatalysis or affecting polypeptide three-dimensional structure [12,38,39], thus ultimately influencing aliment functional properties.…”
Section: Introductionmentioning
confidence: 98%
“…β-Lactoglobulin (β-LGB) and α-lactalbumin (α-LAB) have been identified as main protein reaction targets in dairy products [22]. Their quantitative lactosylation, generally assessed by various MS procedures, has been widely used to monitor milk quality and thermal history [22][23][24][25][26][27][28][29][30][31]; for example, it has been demonstrated that the lactosylated protein forms account for almost 3, 30 and 70% of the β-LGB content in pasteurized, UHT and dry infant formula samples, respectively. Caseins (CSNs) have also been reported as lactosylated species depending on milk thermal treatment [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, this aspect has a high relevance in physiology, food chemistry, and nutrition science. Indeed, Amadori compounds are produced during thermal processing of foods (Biemel et al 2001;Meltretter et al 2009;Schwietzke et al 2011), while some foods, like milk, contain already significant glycation levels in the raw state (Ahmed et al 2005;Meltretter et al 2009). Although early glycation products do not appear to have physiological effects (Miyata and Sprague 1996), the sugar moieties can be involved in glycoxidation (Ahmed et al 1986) or reversal of the Amadori rearrangement followed by the Namiki pathway (Hayashi and Namiki 1980) or autoxidation of the liberated sugar (Wolff and Dean 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The relative amount of BDAB-modified (quinoxaline) lysozyme was calculated by dividing the sum of the intensities of BDAB-modified protein signals by the sum of the intensities of native, glucose-and BDAB-modified protein signals. Such an approach for relative quantification has been proposed by Kislinger et al [39] and has been successfully applied for the relative quantification of protein modifications on peptide [39] or proteins level [40]. Basic principle of this data treatment is the assumption that limited glycation does not influence the electro spray ionization properties of a protein, which means that the ESI-MS response of native and modified species is identical and thus reflects their concentration in the sample [41].…”
Section: Resultsmentioning
confidence: 99%